(335) List of Publications Issued by The I.N.P.C. قائمة المنشورات الصادرة عن المؤسسة الوطنية الهندية للصناعات البترولية. - the technical office. (The Institute Of National Planning., 2018)
the institution of national planning has adopted a temporary policy of publication. documents of varied nature and level are reproduced in outside. such documents include research reports, teaching material conference papers and current reports.